Colors Straight Up - Ohayon, Michèle; Laskus, Jacek; VanDeSande, Theo (New Video, 2005)
Vibrantly engrossing and powerful, Academy Award nominee "Colors Straight Up" offers a wholly inspiring and penetrating look at the lives of inner-city children who are beating the odds through music, acting and dancing. An in-depth document of the lives of teenagers from South Central Los Angeles, the film follows these kids as they struggle to stay off their violent streets and find a better life. Despite the hard and destructive influences which surround them, these teens rediscover their talents and self dignity through Colors United, a performing arts group for inner city kids. On this safe stage, Latino and black kids put down their guns and pick up Shakespeare plays, while finding a second family to provide support and encouragement as they strive to seize more from life. This uplifting and emotional documentary follows this spirited collective throughout a year of obstacles and successes, laughs and tears, dances and funerals, providing unusually intimate depth into their personal and emotional struggle against overwhelming circumstances. Affectionately directed by acclaimed filmmaker Michele Ohayon, "Colors Straight Up" offers powerful insight into the thoughts and feelings of at-risk children everywhere, and inspires others to follow in their footsteps. [Cover]